Design Of An Optical Receiver For The Fiber To The Home (Ftth) Switch - Yaakob, Mohd Hanif (2002)
Fiber to the home (FTTH) architecture provides the full set optical telecommunication services (narrowband and broadband) up to customer premises across the local access services. The main challenge to the realization of FTTH is the cost. However, as the installation cost of the optical fiber technology decreases, FTTH started to gain its reputation as the future communication infrastructure. Once implemented, FTTH architecture needs to maintain its reliability and connectivity. These responsibilities are given to FTTH switch; a network device in the FTTH network that provides very fast inter-connectivity and excellent backup features. One main component of the switch is the optical receiver to receive the optical signal from any locations, either from the central office or the premises and convert the signal to its electrical form to be processed by the switch. Therefore, the objective of the research is to design the optical receiver for the FTTH switch. In this thesis, the intended bandwidth by the receiver is specified at 155 MHz. The other performance parameters concerned are signal to noise ratio (SNR) and sensitivity . The main components of the receiver are PIN photodetector, transimpedance amplifier and post amplifier. PIN photo detector is used as the optical detector to convert the optical signal into its electrical form. Meanwhile, trans impedance amplifier is the photo current to voltage converter. The function of the post amplifier is to amplify the electrical signal. Besides that, additional circuit configuration and topology are applied to improve the performance of the receiver. The optical receiver design was broken into a few modules. Each of them was developed step by step based on two approaches. They are software simulation and hardware implementation (experiment). The receiver performance was analysed based on the results produced by each approach. The final results on the optical receIver system show that the performance standard (I55 MHz bandwidth) was achieved by the simulation approach. However the experiment only manage to support the bandwidth around 126 MHz. The SNR and sensitivity measured from the experimental circuit also give a lower performance compared to the simulation. Based on the experimental results, a few solutions are suggested to increase the optical receiver performance. Meanwhile, the application of the designed optical receiver in the other area is also investigated.